Noninvasive prenatal screening at low fetal fraction: comparing whole‐genome sequencing and single‐nucleotide polymorphism methods. (26th April 2017) - Artieri, Carlo G.; Haverty, Carrie; Evans, Eric A.; Goldberg, James D.; Haque, Imran S.; Yaron, Yuval; Muzzey, Dale
Abstract: Objective: Performance of noninvasive prenatal screening (NIPS) methodologies when applied to low fetal fraction samples is not well established. The single‐nucleotide polymorphism (SNP) method fails samples below a predetermined fetal fraction threshold, whereas some laboratories employing the whole‐genome sequencing (WGS) method report aneuploidy calls for all samples. Here, the performance of the two methods was compared to determine which approach actually detects more fetal aneuploidies. Methods: Computational models were parameterized with up‐to‐date published data and used to compare the performance of the two methods at calling common fetal trisomies (T21, T18, T13) at low fetal fractions. Furthermore, clinical experience data were reviewed to determine aneuploidy detection rates based on compliance with recent invasive screening recommendations. Results: The SNP method's performance is dependent on the origin of the trisomy, and is lowest for the most common trisomies (maternal M1 nondisjunction). Consequently, the SNP method cannot maintain acceptable performance at fetal fractions below 3%. In contrast, the WGS method maintains high specificity independent of fetal fraction and has >80% sensitivity for trisomies in low fetal fraction samples. Conclusion: The WGS method will detect more aneuploidies below the fetal fraction threshold at which many labs issue a no‐call result, avoiding unnecessary invasive procedures. © 2017 Counsyl Inc. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The two most popular noninvasive prenatal screening (NIPS) methodologies, the single nucleotide polymorphism (SNP) and the whole‐genome sequencing (WGS) methods, report comparable performance. However, failure rates vary by an order of magnitude between methodologies. A large component of failure is insufficient fetal fraction, creating "no‐call" test results. The American Congress of Obstetricians and Gynecologists (ACOG) indicates that reported sensitivity is often inflated due to exclusion of failed samples from calculations. What does this study add? The SNP method performs poorly at low fetal fraction on the most common fetal trisomy (maternal M1 nondisjunction). Offering invasive testing to all cases of "no‐call" results will increase the rate of procedure‐related loss. Compared to the SNP method, the WGS method maintains high specificity and can detect a higher proportion of aneuploidies in low fetal fraction samples without unnecessary invasive tests.